Indentation fracture behaviour of fibre metal laminates based on kenaf/epoxy - Abdullah, Mohamed Ruslan (2013)
This paper deals with experimental investigations of fibre metal laminates (FMLs) based on kenaf/epoxy under static indentation loading. Tests were conducted on 2/1 lay-up and 3/2 lay-up of FMLs that fabricated by using vacuum infusion process and hydraulic pressing technique. Indentation tests of FMLs were conducted with loading rate of 10 mm/min. The front and rear surfaces of indentation-loaded FMLs were examined to identify the failure mechanisms at different configurations. It was found that, the failure was happened on the surface of pure kenaf by increasing the indentation depth. However, debonding between the aluminium sheet and kenaf/epoxy is occurred only for 3/2 lay-up of FMLs. The contact force-displacement curves and energy absorption-displacement curves were analysed. The resistance to deform and damage was increase by increasing the number of layers and thickness of aluminium alloy sheet.